`(2x-1)/2 – (1) =( x^2+x-3 )/(x-1)-(5x-2)/(2-2x)`

Question

`(2x-1)/2 – (1) =( x^2+x-3 )/(x-1)-(5x-2)/(2-2x)`

in progress 0
Eloise 34 phút 2021-09-07T10:39:55+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-09-07T10:41:37+00:00

    $\text{Đáp án + Giải thích các bước giải:}$

    `(2x-1)/(2)-1=(x^{2}+x-3)/(x-1)-(5x-2)/(2-2x)` `(ĐKXĐ:x\ne1)`

    `<=>((2x-1)(x-1))/(2(x-1))-(2(x-1))/(2(x-1))=(2(x^{2}+x-3))/(2(x-1))+(5x-2)/(2(x-1))`

    `=>(2x-1)(x-1)-2(x-1)=2(x^{2}+x-3)+5x-2`

    `<=>2x^{2}-2x-x+1-2x+2=2x^{2}+2x-6+5x-2`

    `<=>2x^{2}-5x+3=2x^{2}+7x-8`

    `<=>2x^{2}-2x^{2}-5x-7x=-8-3`

    `<=>-12x=-11`

    `<=>x=(11)/(12)(TM)`

    `\text{Vậy}` `S={(11)/(12)}`

     

    0
    2021-09-07T10:41:44+00:00

    Đáp án:

    `\text{S=}“ {\frac{11}{12}}` 

    Giải thích các bước giải:

    `(2x-1)/2-1=(x^2+x-3)/(x-1)-(5x-2)/(2-2x) \ \ \ \ (x ne 1)`

    `<=> ((2x-1)(x-1))/(2(x-1))-(2(x-1))/(2(x-1))=(2(x^2+x-3))/(2(x-1))+(5x-2)/(2(x-1))`

    `=> (2x-1)(x-1)-2(x-1)=2(x^2+x-3)+5x-2`

    `<=> 2x^2-3x+1-2x+2=2x^2+2x-6+5x-2`

    `<=> 2x^2-5x+3=2x^2+7x-8`

    `<=> 2x^2-2x^2-5x-7x=-8-3`

    `<=> -12x=-11`

    `<=> x=11/12 \ \ \ \ text{(tm)}`

    `\text{Vậy S=}“ {\frac{11}{12}}`

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )